Swansea Copper : A Global History - Evans, Chris, 1961-; Miskell, Louise (Book collections on Project MUSE., 2020)
"This is a history of copper as a commodity, which focuses on copper produced in Swansea, Wales, and sold around the world. Between the 1770s and the 1840s, the Swansea district produced nearly half of the world's smelted copper. This book traces the history of copper making in Britain beginning in the late seventeenth century, when a technological breakthrough set Britain on a course to becoming the world's biggest producer of smelted copper. The book shows how deeply mineral history is engrained in the history of the modern world"--